Behavioral phenotypes of childhood idiopathic epilepsies. (18th June 2020) - Hermann, Bruce P.; Struck, Aaron F.; Stafstrom, Carl E.; Hsu, David A.; Dabbs, Kevin; Gundlach, Carson; Almane, Dace; Seidenberg, Michael; Jones, Jana E.
Abstract: Objective: To characterize the presence and nature of discrete behavioral phenotypes and their correlates in a cohort of youth with new and recent onset focal and generalized epilepsies. Methods: The parents of 290 youth (age = 8‐18 years) with epilepsy (n = 183) and typically developing participants (n = 107) completed the Child Behavior Checklist for children aged 6‐18 from the Achenbach System of Empirically Based Assessment. The eight behavior problem scales were subjected to hierarchical clustering analytics to identify behavioral subgroups. To characterize the external validity and co‐occurring comorbidities of the identified subgroups, we examined demographic features (age, gender, handedness), cognition (language, perception, attention, executive function, speed), academic problems (present/absent), clinical epilepsy characteristics (epilepsy syndrome, medications), familial factors (parental intelligence quotient, education, employment), neuroimaging features (cortical thickness), parent‐observed day‐to‐day executive function, and number of lifetime‐to‐date Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM‐IV) diagnoses. Results: Hierarchical clustering identified three behavioral phenotypes, which included no behavioral complications (Cluster 1, 67% of epilepsy cohort [n = 122]), nonexternalizing problems (Cluster 2, 11% of cohort [n = 21]), and combined internalizing and externalizing problems (Cluster 3, 22% of cohort [n = 40]). These behavioral phenotypes were characterized by orderly differences in personal characteristics, neuropsychological status, history of academic problems, parental status, cortical thickness, daily executive function, and number of lifetime‐to‐date DSM‐IV diagnoses. Cluster 1 was most similar to controls across most metrics, whereas Cluster 3 was the most abnormal compared to controls. Epilepsy syndrome was not a predictor of cluster membership. Significance: Youth with new and recent onset epilepsy fall into three distinct behavioral phenotypes associated with a variety of co‐occurring features and comorbidities. This approach identifies important phenotypes of behavior problem presentations and their accompanying factors that serve to advance clinical and theoretical understanding of the behavioral complications of children with epilepsy and the complex conditions with which they co‐occur.